Age features of lipid peroxidation and antioxidant protection processes in girls and women tofalar ethnic groups - L. I. Kolesnikova; M. A. Darenskaya; V. V. Dolgikh; V. A. Shenin; S. V. Dutova; L. A. Grebenkina; M. I. Dolgikh (Бюллетень сибирской медицины)
Research objective: studying lipid peroxidation and antioxidant protection processes in girls and women of 3 age groups living in Tofalariya (ethnic tofalars). Spectrophotometric, fluorometric and statistic methods (Student’s parametrical criterion and Fisher's coefficient) were used. It was determined that decrease of lipid peroxidation and antioxidant protection processes activity takes place in puberty period. We marked increase concentration of lipid peroxidation products and retinol. The elder age period is characterized by the raised intensity of peroxidation processes.